Clinical usefulness of new noninvasive serum biomarkers for the assessment of liver fibrosis and steatosis in children with chronic hepatitis C - Pokorska-Śpiewak, Maria; Kowalik-Mikołajewska, Barbara; Aniszewska, Małgorzata; Pluta, Magdalena; Marczyńska, Magdalena (Clinical and Experimental Hepatology, 2017)
Aim of the study : Recently, novel serum markers modified by the body mass index z-score (BMI z-score) were proposed as a reliable noninvasive alternative for the detection of significant fibrosis and steatosis in children with chronic hepatitis C (CHC). The aim of this study was to evaluate the clinical usefulness of these biomarkers. Material and methods : Thirty children aged 9.4 ± 3.7 years (14 males, 16 females) with CHC were included in this study. In all patients, histopathological evaluation of the liver fibrosis was performed using a 5-point METAVIR scoring system (≥ 2 points = significant fibrosis). Significant steatosis was diagnosed with > 33% of hepatocytes affected. The following noninvasive markers of liver disease were calculated: the modified aspartate transaminase (AST)-to-platelet ratio index (M-APRI: BMI z-score × APRI), the modified Fibrosis-4 index (M-FIB-4: BMI z-score × FIB-4), and a novel marker, B-AST (BMI z-score × AST). The clinically useful cut-offs for each marker were selected as simple round numbers, indicating significant fibrosis and steatosis. Results : Significant fibrosis was detected in 7/30 (23%) cases, and significant steatosis was observed in 4 (13%) patients. Comparison with the histopathological evaluation revealed that B-AST < 0 excluded significant fibrosis, and < 100 excluded all patients with significant steatosis. For the M-APRI, < 0 excluded significant fibrosis, and < 0.5 excluded significant steatosis. For the M-FIB-4, < 0 excluded significant fibrosis and < 0.2 excluded significant steatosis. Conclusions : Negative values of all three markers that included the BMI z-score excluded all patients with both significant fibrosis and significant steatosis.